Immunohistochemical Distribution of Somatostatin, Glucagon and Gastrin in the Gastric Fundus of the Citellus (Spermophilus xanthoprymnus) - Timurkaan, Sema; Timurkaan, Necati; Ozkan, Ender; Girgin, Mustafa (Medwell Online, 2009)
The distribution of endocrine cells in the fundus of the citellus (Spermophilus xanthoprymnus) was investigated using immunohistochemical PAP (Peroxidase-Antiperoxidase) method. Three types (somatostatin, glucagon, gastrin) of immunoreactive endocrine cells were identified in this study. They were spherical or spindle-shaped. Moderate number gastrin immunoreactive cells were identified in the fandus. Closed type gastrin immunoreactive cells were exclusively located in the basal portion of the fundic region, but occasionally open type cells were found mixed with closed type cells. Somatostatin immunoreactive cells were restricted to the fundus with few and moderately frequencies. They were dispersed in the whole gastric mucosa, between chief and parietal cells. However, closed type cells were exclusively located in the basal portion of the fundic mucosa, but occasionally open type cells were found mixed with close type cells. Closed type glucagon immunoreactive cells were restricted to the basal portion of the fandic mucosa with a few frequencies. Immunocytochemical localization of the glucagon, gastrin and somatostatin in the gastrointestinal tract of the Spermophilus xanthoprymnus was described for the first time in the present study. This study showed similarity to that observed in the rat and mammalian species.
Keywords: Anatolian souslik; immunohistochemistry; fundus; gastrin; somatostatin; glucagon